Linear measurement of cell contraction in a capillary collagen gel system. (February 2010) - Ilagan, Roger M.; Guthrie, Kelly I.; Quinlan, Sarah F.; Rapoport, H. Scott; Jones, Sarah; Church, Ashley; Basu, Joydeep; Ludlow, John W.
Three-dimensional collagen gel contraction is the standard assay utilized for functionally quantifying a variety of cell types, in particular smooth muscle cells (SMCs) and myofibroblasts. Here, we have developed a method to effectively reduce the three-dimensional parameters of the standard collagen gel into a single, linear measurement. Cell/collagen suspensions that are cast into glass capillary tubes provide several advantages over the well plate format, such as eliminating the need for digital imaging equipment and software to quantify the amount of cellular contraction. In addition, capillary tube gels require significantly fewer cells and far less reagents than standard methods.